Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.99
|View full text |Cite
|
Sign up to set email alerts
|

Sparsifying Distributed Algorithms with Ramifications in Massively Parallel Computation and Centralized Local Computation

Abstract: We introduce a method for "sparsifying" distributed algorithms and exhibit how it leads to improvements that go past known barriers in two algorithmic settings of large-scale graph processing: Massively Parallel Computation (MPC), and Local Computation Algorithms (LCA). • MPC with Strongly Sublinear Memory: Recently, there has been growing interest in obtaining MPC algorithms that are faster than their classic O(log n)-round parallel (PRAM) counterparts for problems such as Maximal Independent Set (MIS), Maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 30 publications
(32 reference statements)
0
104
1
Order By: Relevance
“…2 Corollary 1.2 exponentially improves over this bound. 2 We comment that although it is unclaimed, a recent algorithm of Ghaffari and Uitto [21] can also be simulated in the congested clique model leading to an O( √ log ∆) round algorithm. Corollary 1.3.…”
Section: Resultsmentioning
confidence: 99%
“…2 Corollary 1.2 exponentially improves over this bound. 2 We comment that although it is unclaimed, a recent algorithm of Ghaffari and Uitto [21] can also be simulated in the congested clique model leading to an O( √ log ∆) round algorithm. Corollary 1.3.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the LCA results we pointed to above, close to our work are [RTVX11, ARVX12, LRY17, Gha16, GU19] who also study the worst-case oracle behavior. In particular, [GU19] showed that there exists an oracle that given an arbitrary chosen vertex v outputs whether v is in some fixed maximal independent set or not by performing d O(log log d) · poly log n queries. When this oracle is applied to the line graph, then it reports whether a given edge is in a fixed maximal matching or not.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, [GU19] showed that there exists an oracle that given an arbitrary chosen vertex v outputs whether v is in some fixed maximal independent set or not by performing d O(log log d) · poly log n queries, which improves on the prior work obtaining d O(poly log d) · poly log n complexity [RTVX11, ARVX12, LRY17,Gha16]. When this oracle is applied to the line graph, then it reports whether a given edge is in a fixed maximal matching or not.…”
Section: Related Workmentioning
confidence: 99%
“…In a follow-up work, [BBD + 19] devise MIS and matching algorithms in uniformly sparse graphs in O(log 2 log n) rounds. In independent concurrent works, Ghaffari and Uitto [GU19] and Onak [Ona18] provide algorithms for the problems of maximal independent set and matching in general graphs in O( √ log n) rounds. In [CFG + 18], Chang et al develop an O( √ log log n)round low-memory MPC algorithm for (∆ + 1)-list coloring.…”
Section: Low-memory Mpc Model For Graph Problemsmentioning
confidence: 99%